Genotypic Variation in Yield, Yield Components, Root Morphology and Architecture, in Soybean in Relation to Water and Phosphorus Supply - He, Jin; Jin, Yi; Du, Yan-Lei; Wang, Tao; Turner, Neil C.; Yang, Ru-Ping; Siddique, Kadambot H. M.; Li, Feng-Min (Frontiers in Plant Science, 2017)
Water shortage and low phosphorus (P) availability limit yields in soybean. Roots plays important roles in water-limited and P-deficient environment, but the underlying mechanisms are largely unknown. In this study we determined the responses of four soybean varieties (Huandsedadou (HD), Bailudou (BLD), Jindou 21 (J21) and Zhonghuang 30 (ZH)) to three P levels [applied 0 (P0), 60 (P60) and 120 (P120) mg P kg–1 dry soil to the upper 0.4 m of the soil profile] and two water treatment [well-watered (WW) and water-stressed (WS)] with special reference to root morphology and architecture, we compared yield and its components, root morphology and root architecture to find out which variety and/or what kind of root architecture had high grain yield under P and drought stress. The results showed that water stress and low P, respectively, significantly reduced grain yield by 60 % and 40 %, daily water use by 66 % and 31 %, P accumulation by 40 % and 80 %, and N accumulation by 39 % and 65 %. The cultivar ZH with the lowest daily water use had the highest grain yield at P60 and P120 under drought. Increased root length was positively associated with N and P accumulation in both the WW and WS treatments, but not with grain yield under water and P deficits. However, in the WS treatment, high adventitious and lateral root densities were associated with high N and P uptake per unit root length which in turn was significantly and positively associated with grain yield. Our results suggest that (1) genetic variation of grain yield, daily water use, P and N accumulation and root morphology architecture were observed among the soybean cultivars and ZH had the best yield performance under P and water limited conditions; (2) water has a major influence on nutrient uptake and grain yield, additional P supply can modestly increase yields under drought in some soybean genotypes; (3) while conserved water use plays an important role in grain yield under drought, root traits also contribute to high nutrient uptake efficiency and benefit yield under drought.